A stream function approach to real-time path planning for mobile robots - Orcullo, Gemi P. (2001)
This paper suggests an alternative to the potential field method for solving real-time path planning problems. Motivated by fluid flow phenomenon, stream functions are used to generate paths that are not constrained by local minimal problems inherent in potential field-based methods. The stream function defines the path of an ideal fluid particle in a laminar flow, that is, a streamline. In this study, the proposed algorithm is tested under different conditions to determine its performance on static and dynamic environments. Simulation results demonstrate the effectiveness of the proposed method and its applicability to real-time situations.